A new method for encapsulating hydrophobic compounds within cationic polymeric nanoparticles. (14th March 2013) - Ben Yehuda Greenwald, Maya; Ben Sasson, Shmuel; Bianco-Peled, Havazelet
Abstract : Here we present the newly developed "solvent exchange" method that overcomes the challenge of encapsulating hydrophobic compounds within nanoparticle of water soluble polymers. Our studies involved the model polymer polyvinylpyrrolidone (PVP) and the hydrophobic dye Nile red. We found that the minimum molecular weight of the polymer required for nanoparticle formation was 49 KDa. Dynamic Light Scattering (DLS) and Cryo-Transmission Electron Microscopy (cryo-TEM) studies revealed spherical nanoparticles with an average diameter ranging from 20 to 33 nm. Encapsulation efficiency was evaluated using UV spectroscopy and found to be around 94%. The nanocarriers were found to be highly stable; less than 2% of Nile red release from nanoparticles after the addition of NaCl. Nanoparticles containing Nile red were able to penetrate into glioma cells. The solvent exchange method was proved to be applicable for other model hydrophobic drug molecules including ketoprofen, ibuprofen and indomethacin, as well as other solvents.